Chaos as an intermittently forced linear system - Steven L. Brunton (Nature Portfolio, 2017)
The huge amount of data generated in fields like neuroscience or finance calls for effective strategies that mine data to reveal underlying dynamics. Here Brunton et al.develop a data-driven technique to analyze chaotic systems and predict their dynamics in terms of a forced linear model.